Age at castration (surgical or immunological) impacts carcass characteristics and meat quality of male pigs. (14th August 2017) - Huber, L.; Squires, E. J.; Mandell, I. B.; de Lange, C. F. M.
Abstract : In order to accurately estimate body composition at slaughter and to meet specific market targets, the influence of age at time of castration (surgical or immunological) on body composition and boar taint indicators must be determined for male pigs. In all, 48 males were randomly assigned to one of four management regimens: (1) entire male pigs (EM), (2) EM surgically castrated at 40 kg BW and 10 weeks of age (late castrates; LC), (3) conventional, early surgical castrates (within 4 days of birth; EC) and (4) EM immunized with a gonadotropin-releasing hormone (GnRH) analog (primary dose at 30 kg BW and 8 weeks of age; booster dose at 70 kg and 14 weeks of age; IM). Pigs were fed corn and soybean meal-based diets that were not limiting in essential nutrients. Back fat was sampled on days −3, 8, 18 and 42, relative to administering the booster dose of GnRH analog at day 0, to determine androstenone concentrations ( n =8 or 9/group). Fat androstenone concentrations in IM were lower than EM between days 8 and 42 after administering the booster dose (173 v . 863 ng/g, respectively; P <0.01), and were not different from surgically castrated males (EC and LC) after day 18. Slaughter occurred at 115 kg BW, 42 days (6 weeks) after administering the booster dose for IM, and 10 and 20 weeks after surgical castration for LC and EC, respectively ( n =8 or 9/group). At slaughter, live BW, liver weight as a percent of live BW, dissectible bone as a percent of cold carcass side, body protein and water contents and whole-body protein deposition decreased with time after surgical castration (linear; P <0.05), whereas dressing percentage, dissectible fat, probe fat depth and body fat content increased with time after surgical castration (linear; P <0.05). The IM had intermediate dressing percentage and dissected fat to EM and EC, whereas liver weight as a percent of live BW and body protein and lipid contents were not different from EM. Whole-body lipid deposition tended to be greater in IM than in EM between 14 and 20 weeks of age (373 v . 286 g/d; P= 0.051). In conclusion, castration of male pigs after 6 weeks of age has a lasting effect on physical and chemical body composition. The relationship between time after castration and body composition may be developed to predict carcass composition and can be used to determine the ideal immunization schedule aimed at specific markets in the future.